POTENSI WISATA KABUPATEN KERINCI DALAM KARYA SENI LUKIS IMPRESIONIS - Drs. Erfahmi, M.Sn., YAYUK KARTINI, Drs. Abd. Hafiz, M.Pd, (Serupa The Journal of Art Education, 2017)
This thesis aims to visualize Kerinci tourism potential into impressionist painting, as an effort to socialize tourism potential revealed from nature, culture, history, until the typical culinary Kerinci. Methods in realizing the ideas of art: preparation, elaboration, synthesis, realization of the concept and completion. This work describes the potential of nature tourism, building or historic objects, tradisional dance, food to handicrafts Kerinci.Kata kunci: Wisata, Kerinci, Seni Lukis Impresionis